Project based Learning Using Student Clubs and Short Online Videos, In-class Activities - Demir, Yakup; Ucar, Aysegul (Ieee, 2016)
This paper presents a project based learning approach applied to the teaching of the Fundamentals of Electrical and Electronics Engineering (FEEE). The training is composed of several modules such as the in-class activities, practical student activities or courses organized by student clubs, learning materials, term project usable as product in real life, short exams, and homework assignments. The proposed approach allows students to better understand circuit components and circuit principles. In this paper, three projects are presented as examples of project based learning using student clubs. The students successfully completed their all projects. Especially they generated a specific prototype for the term projects. All results were evaluated and success of the students were presented.
15th International Conference on Information Technology Based Higher Education and Training (ITHET) -- SEP 08-10, 2016 -- Istanbul, TURKEY
Keywords: Project-based learning; Student Clubs; In-class activities; Short Online Videos